2020
DOI: 10.1029/2020jd032418
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Trends and Solar Responses of the Mesopause Temperatures Observed by SABER During the 2002–2019 Period

Abstract: The global distribution and variations of the monthly mesopause temperature are presented during 2002–2019 covering the latitudes of 83°S to 83°N based on Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) observations. To investigate the long‐term trend and solar response of the mesopause temperature, a three‐component harmonic fit is first applied to remove the seasonal variation from the monthly temperature data series. Then a multiple linear regression model is performed to residual tem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 55 publications
(105 reference statements)
6
12
1
Order By: Relevance
“…At high latitudes, the long-term trends in peak altitude diminish. This contrasts with reports that broadly indicate the strongest trends in temperature, mesospheric O 3 , and water vapor occur at high latitudes (Dawkins et al, 2016;Hervig et al, 2016;Zhao et al, 2020), albeit all with larger uncertainties. This behavior, and the hemispheric asymmetry in linear trend responses reported here and in Qian et al (2017), Sharma et al (2018), and Das (2021) suggest a role for dynamics, particularly at high latitudes.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…At high latitudes, the long-term trends in peak altitude diminish. This contrasts with reports that broadly indicate the strongest trends in temperature, mesospheric O 3 , and water vapor occur at high latitudes (Dawkins et al, 2016;Hervig et al, 2016;Zhao et al, 2020), albeit all with larger uncertainties. This behavior, and the hemispheric asymmetry in linear trend responses reported here and in Qian et al (2017), Sharma et al (2018), and Das (2021) suggest a role for dynamics, particularly at high latitudes.…”
Section: Discussioncontrasting
confidence: 97%
“…This is consistent with the work of Yuan et al (2019), Bailey et al (2021), Mlynczak et al (2022), and modeling studies which have demonstrated hydrostatic contraction of the middle and upper atmosphere in response to increasing GHG emissions (Roble and Dickinson, 1989;Akmaev et al, 2006;Lübken & Berger, 2011). The linear response in peak altitude was relatively small at low latitudes and increased toward the mid-latitudes, consistent with work by Zhao et al (2020Zhao et al ( , 2021.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A model proposed by Matthes, Langematz [9] suggested that the solar influence on the mesopause region to be minimal. This knowledge is supported by numerous studies conducted prior and subsequent to it [10][11][12][13]. In a recent study, simulations presented by Solomon, Liu [14] has demonstrated that low solar activity periods show greater impact on long-term global changes in the thermosphere and ionosphere as compared to high solar activity periods.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, Zhao et al. (2020) detected a cooling trend of ∼0 to −0.14 K/decade at all latitudes using the annual mean temperatures from Sounding of the Atmosphere Using Broadband Emission Radiometry (SABER) instrument from 2002 to 2019. Li et al.…”
Section: Introductionmentioning
confidence: 99%